Prevalence and Pattern of Hearing Loss among Head and Neck Cancer Patients Receiving Chemotherapy with or without Radiation Therapy at Ocean Road Cancer Institute, Tanzania (Tanzania Medical Journal, 2021)
Background Head and neck cancers are primarily treated by three main modalities; surgery, radiotherapy and chemotherapy administered alone or in combination. Radiotherapy and chemotherapy may cause complications to patients including hearing loss with various outcomes on types and severity.Broad objectiveTo determine the prevalence and pattern of hearing loss among head and neck cancer patients receiving chemotherapy with or without radiation therapy at Ocean Road Cancer Institute, Tanzania.Methodology This was a hospital based descriptive cross sectional study which included 138 histopathological confirmed head and neck cancer patients from June to December 2017. Data collected using structured questionnaires included demographic characteristics, site of the tumor, treatment modality, type of chemotherapy groups used, dosage and duration. Pure tone audiometry at a frequency range of 250HZ to 8000HZ using Amplivox 270 audiometer was performed to all patients after otoscopy. Data was analyzed using Statistical Package for Social Science version 20 and a p value of <0.05 was considered to be statistically significant. ResultsOut of 138 patients who were involved in the study, 98(71%) had hearing loss. Among 98 patients who had hearing loss, 53(54.1%) received chemotherapy alone and all had sensorineural hearing loss, the remaining 45(45.9%) patients received concurrent chemoradiation and 40(88.9%) had sensorineural hearing loss. Conductive and mixed hearing loss were observed in 3 (6.7%) and 2 (4.4%) patients who received chemoradiation, respectively (p value = 0.045). The severity of sensorineural hearing loss was higher among patients who received chemoradiation than those who received chemotherapy alone (p value =0.682). Use of a single drug group or combined drug groups had no significant difference in terms of outcomes on severity of hearing loss (p value =0.603) but high cumulative doses of platinum and taxane compounds had significant increase in terms of outcomes on severity of hearing loss. (p value =0.003, 0.021 respectively).Conclusion and recommendationHearing loss following chemotherapy alone or with concurrent chemoradiation therapy is quite prevalent in our settings thus hearing evaluation pre, during and post chemotherapy/radiotherapy is encouraged for earlier detection of hearing loss and establishing prompt intervention.